OCP Oracle Certified Professional Java SE 8 Programmer II study guide : exam 1Z0-809 - Boyarsky, Jeanne; Selikoff, Scott (Sybex, 2016)
OCP: Oracle Certified Professional Java SE 8 Programmer II Study Guide is your comprehensive companion for preparing for Exam 1Z0-809 as well as upgrade Exam 1Z0-810 and Exam 1Z0-813. With full coverage of 100% of exam objectives, this invaluable guide reinforces what you know, teaches you what you don't know, and gives you the hands-on practice you need to boost your skills. Written by expert Java developers, this book goes beyond mere exam prep with the insight, explanations and perspectives that come from years of experience. You'll review the basics of object-oriented programming, understand functional programming, apply your knowledge to database work, and much more. From the basic to the advanced, this guide walks you through everything you need to know to confidently take the OCP 1Z0-809 Exam and upgrade exams 1Z0-810 and 1Z0-813.